2022
DOI: 10.1038/s41598-022-06094-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between birth weight and neurodevelopmental disorders assessed using the Korean National Health Insurance Service claims data

Abstract: The risk of neurodevelopmental disorders in low birth weight (LBW) infants has gained recognition but remains debatable. We investigated the risk of attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) in school-aged children according to their birth weight. We conducted a retrospective cohort study using the Korean National Health Insurance claims data of 2,143,652 children who were born between 2008 and 2012. Gestational age of infants was not available; thus, outcomes were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Similar findings were found in different studies done by Hisle-Gorman, Gardener et al and Guinchat et al 15,28,29 While, low birth weight has been found to be the risk factor of ASD by some authors. 29,30,31 But the present study did not identify low birth weight as the risk factor.…”
Section: Discussioncontrasting
confidence: 78%
“…Similar findings were found in different studies done by Hisle-Gorman, Gardener et al and Guinchat et al 15,28,29 While, low birth weight has been found to be the risk factor of ASD by some authors. 29,30,31 But the present study did not identify low birth weight as the risk factor.…”
Section: Discussioncontrasting
confidence: 78%
“…Socioeconomic inequity impacts access to formal diagnosis, especially for individuals in low-to-middle income socio-economic status (SES). While early diagnosis has been a consistent aim among stakeholders (Freeman et al, 2019;Gu, 2019;Harris et al, 2019;Song et al, 2022), a significant proportion of the low-tomiddle income SES population continues to be unscreened for developmental and mental health disabilities as well as co-occurring medical conditions, particularly POC (Keynejad et al, 2018;Niessen et al, 2018). Burgeoning late diagnosis of a developmental disability (Green et al, 2019;Leedham et al, 2020) indicates six of several underlying problems: 1) lack of access to early screening (Choo et al, 2019);…”
Section: Intersection Of Neurodivergence and Socioeconomic Statusmentioning
confidence: 99%
“…According to our study results birth height was associated with decrease in odds of ASD, however there was no statistically signi cant difference in birth weight between cases and controls. Some authors demonstrated that infants with birth weights of < 2.5 kg were associated with ADHD and ASD 53,54 .…”
Section: Discussionmentioning
confidence: 99%